Morbus Hansen Mimicking Trichoepithelioma with Co-infection of Tuberculous Spondylitis in a Child - Larasati Budiyarto; Devi Arofah Mumtazah; I Ketut Sukarata; Yufanti Sujudi (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Morbus Hansen (Leprosy) is a chronic bacterial infection disease caused by Mycobacterium leprae. According to WHO data in 2020, Indonesia is one of the countries that contributes to the highest number of cases of leprosy in the world. In 2016, there were 18,248 leprosy cases in Indonesia, with a prevalence of 0.71 per 10,000 population. Leprosy presents a challenge in diagnosis, earning it the moniker 'the great imitator' disease Case: A 10-year-old boy presented with skin manifestations of multiple papules and nodules resembling trichoepithelioma on the face, accompanied by erythematous-hyperpigmented plaque on the arm. The histopathology examination of the papule on face revealed orthokeratotic epidermis, clusters of histiocytes and epitheloid cells, foam cells, multiple inflammatory lymphocytes, and a multinucleated giant cell without caseous necrosis, confirming the diagnosis of chronic granulomatous inflammation. The examination revealed acid-fast bacilli. The patient was undergoing treatment for tuberculous spondylitis. The diagnosis was confirmed as multibacillary leprosy and multidrug therapy (MDT) for multibacillary leprosy in children were administered, adjusting the rifampicin dose in accordance with the tuberculous spondylitis treatment. Lesions on the face regressed after two months therapy. Discussion: Diagnosing leprosy based on physical examination is considered tricky due to its varying clinical manifestations and differential diagnosis. It is important for clinicians to acknowledge the diverse skin manifestations of leprosy to detect the disease early and improve treatment outcomes and prognosis.